Determination of the standard cost of raw materials for the activity of extracting crude oil and gas by application in the North Oil Company - حليل جليلة عيدان (Journal of Economics and Administrative Sciences, 2012)
There are many problems facing the economic entities as a result of its mass production &variation of its products , the matter which had increased the need & importance of cost accounting which is regarded a main tool for the managerial control. The actual costing system is unable to meet the contemporary management needs ,so the Standard costing system appear to provide the management with required information to perform its functions by the best use& way. This research aims to determine the standard cost for the direct material for oil extraction activity by applying it in the north oil company.